Out-of-time-order correlation in the quantum Ising Floquet spin system and magnonic crystals - Shukla, Rohit Kumar (IIT(BHU) Varanasi, 2022)
Abstract is available in the content.
Keywords: Out-of-time-order correlation; quantum Ising Floquet spin system; and magnonic crystals